Modeling Global and Local Aspects of Spatial Structure Explicitly in Land-Use Optimization: The Case of Mek’ele City, Ethiopia - Ashenafi MEHARI; Paolo Vincenzo GENOVESE (Chinese Journal of Urban and Environmental Studies, 2023)
Urban spatial structure remains the center of quest and modeling. The decentralization concept is among the leading literature discourses that guide spatial analyses. In line with the decentralization discourse, the application of land-use optimization as a modeling method has grown significantly. Despite decentralization dominating the contemporary spatial analysis literature, no study so far explicitly declares an end to the centers (and subcenters). While centers (and subcenters) are alive, the land-use optimization has never taken this macro-morphological structure into consideration. This case study frames land-use optimization within the agglomeration and decentralization concepts based on the view that no single conceptual framework addresses spatial analysis sufficiently. On a theoretical level, the link is between coarse morphological assumption (basis of economic geography) and decentralization (basis of sustainable built environment). The paper blends these dual theories, one governing urban macro-morphological structures and the other governing decentralization literature. On a methodological modeling level, it blends centers and other discretized uses. Optimizing four objectives across the complete centralization through multiple centers of gravity to complete the decentralization of urban spatial structures applying Non-dominated Sorting Genetic Algorithm II, the case study findings justify the importance of explicit modeling of the macro-morphological element. It has been observed that multicenter urban forms perform well above both the single center and the dispersed scenarios. It is, therefore, argued that an appropriate approach to land-use optimization is modeling both the macro-spatial element and fine spatial elements. The result further indicates that local land-use planning regulations place the structure of city in a suboptimal state.